Running Event “Trackpresso: 5K Color Run 2024 di Kota Semarang, Jawa Tengah” sebagai Creative & Design Manager - Al Ghifari, Rafdil; Luqman, Yanuar; Naryoso, Agus (Interaksi Online, 2024)
This project delves into all the preparations and execution of the Trackpresso: 5k Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the project team based on the desire to create an event that was trending in recent months. As a foundation for this project, this report utilizes the event management framework outlined in Joe Goldblatt's book "Special Events," which details event execution through five stages: research, design, planning, coordination, and evaluation. The Trackpresso: 5K Color Run event targeted 150 participants and was held on August 24th in Semarang. The results of this report indicate that the event was executed as planned, with 150 participants taking part in the Trackpresso: 5K Color Run. In fulfilling the roles of Creative Manager and Production Manager for this event, the team successfully achieved the set targets, including the creation of the event logo, design of Instagram content, and procurement of production goods for each event. Thus, the creation of the event logo, the target of Instagram posts for Olahraga Nusantara from June to August 2024, the procurement of production goods for the MLBB Competition event, and the procurement and sourcing of production goods for the Trackpresso: 5K Color Run 2024 event were all fulfilled. This report recommends that the Trackpresso: 5K Color Run 2024 project can contribute to the academic field by providing a framework for preparing similar events..